Does digital transformation promote innovation performance? Evidence from listed Chinese firms - Jin, Zhiwei; Qin, Jie (Journal of Accounting, Business and Finance Research, 2024)
This study examines the impact of digitalization on firm innovation. Using a comprehensive sample of publicly listed Chinese firms, we construct a micro-level digitalization indicator using a textual analysis of annual financial reports. It was found that digitalization leads to a significant upswing in a firm’s innovative output. Rigorous robustness checks and stability tests were conducted, including variable substitutions and different models, such as the Tobit and Poisson models. Additionally, the study utilizes a treatment effects model to account for unobserved heterogeneity and control for potential biases, ensuring the reliability and validity of the findings. Whether an enterprise is state-owned (SOEs) or non-state owned (non-SOEs), the digitalization of enterprises has dramatically enhanced their innovation capabilities. Digitalization has a significant effect on financially constrained firms. Compared to non-SOEs, the effect of financial constraints is more pronounced among SOEs. Highly digitalized firms also experienced higher growth rates and lower leverage ratios relative to firms with low digitalization, and they are more likely to receive governmental subsidies. Furthermore, the findings suggest that policymakers should prioritize initiatives aimed at promoting digitalization across all sectors of the economy. By fostering an environment conducive to digital innovation, governments can stimulate economic growth and enhance firms’ competitiveness on a global scale. In essence, the study underscores the transformative potential of digitalization in driving innovation and economic progress.